Appendix 4.3: Excerpts from Luneta v. Special Military Commission, G.R. No. L-49473, and the Concurring Opinion by Chief Justice Fernando - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Brazenly, in this decision declaring that, inter alia, the right to speedy trial of the petitioners—all martial law-era detainees—was not violated by the government, Justice Antonio Barredo gave praise—literally to the high heavens—to the president and the first lady. In his short concurring opinion, chief justice Fernando seconded Barredo’s sentiments, though in a more subdued manner. As in other cases concerning abuses of power during martial law, Justice Claudio Teehankee Sr. appended a brief dissenting opinion.